A Scoping Review of Factors Associated with Delayed Extubation in Post Cardiac Surgery Patients - Kumalasari RI; Kosasih CE; Priambodo AP (Vascular Health and Risk Management)
Regina Indah Kumalasari,1 Cecep Eli Kosasih,2 Ayu Prawesti Priambodo2 1Master Study Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Critical Care and Emergency Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, IndonesiaCorrespondence: Cecep Eli Kosasih, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir, Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +6281320941727, Fax +6202287793411, Email cecep.e.kosasih@unpad.ac.idBackground: Delayed extubation (DE) after cardiac surgery is associated with high morbidity, mortality, increased length of stay in the intensive care unit, and hospital costs. Various studies have identified factors that influence the occurrence of DE in patients after cardiac surgery, but no review has systematically synthesized the results.Purpose: This review aimed to identify the influencing factors and the leading causes of DE in patients after cardiac surgery.Methods: This scoping review uses the framework developed by Arksey and O’Malley (2005). Literature was searched through four databases: PubMed, Scopus, Science Direct, and CINAHL, and two search engines, Sage and Google Scholar, accessed on October 20, 2024. The articles analyzed met the inclusion criteria, such as full-text articles in English, published from 2014– 2024, with case-control, cross-sectional, longitudinal, and cohort study designs and had good quality as assessed using the Joanna Briggs Institute critical appraisal checklist. Data was synthesized using thematic analysis.Results: Eight articles with a total of 13801 participants were included in this review. The prevalence of DE after cardiac surgery ranged from 13.6% to 91.9%. The factors affecting DE were categorized into preoperative, intraoperative and postoperative. The factors most commonly reported to influence ED include preoperative factors (age ≥ 60 and EF < 50%), intraoperative factors (duration of surgery ≥ 7 hours, use of IABP and sedatives), and postoperative factors (BNP≥ 806 pg/mL). The leading causes of DE after cardiac surgery are hemodynamic instability requiring increased inotropes (33.51%), reduced level of consciousness or drowsiness (31.91%), and postoperative bleeding (20.74%).Conclusion: The process of extubation is a crucial phase in postoperative care. By comprehending the elements that impact DE, healthcare providers can effectively allocate medical resources to enhance the success of weaning, extubation, and recovery following cardiac surgery. Consequently, further research focusing on DE is essential, particularly in patients who have undergone cardiac surgery.Keywords: cardiac surgery, delayed extubation, mechanical ventilation